EFEKTIVIAS EKOENZIM TERHADAP KELULUSHIDUPAN IKAN LELE (Clarias sp.) PADA MEDIA YANG TERCEMAR LIMBAH BATIK - Nia Ardianita; Riska Andriani; Nadya Puspita Maya (Prodi Biologi Universitas PGRI Ronggolawe, 2023)
Ecoenzymes are active substances that can accelerate the degradation process of waste and improve the quality of the environment. The benefits of ecoenzymes for the environment, particularly in agriculture as fertilizer, and in households as a germ and bacteria killer are very good. It is hoped that ecoenzymes can neutralize batik waste, which is toxic to aquatic environments. This study aims to evaluate the effectiveness of ecoenzymes on the survival rate of catfish (Clarias sp.) in media contaminated with batik waste. The method used is an experiment using three concentrations of ecoenzymes and measuring the sustainability of catfish life at each concentration. Based on the results of the research, catfish that were exposed to batik waste and added with ecoenzymes with concentrations of 0% and 10% showed that the catfish could not survive. This shows that ecoenzymes have not yet been proven to increase the effectiveness in neutralizing batik waste against the survival rate of catfish (Clarias sp.).